THE INFLUENCE OF TRADITIONAL VALUES IN CHINESE REASONING (A Case – Study) - Butucea, Maria (European Scientific Journal, ESJ, 2013)
In this case-study we try to emphasise how traditional value as mental programs can be find in a modern Chinese life and teaching. Using anthropological and ethnological methods we can better understand the universal reasoning and also, if they are, some differences, how they are operating in different areas and why? We made observation in Chinese culture and tried to compare them with western logic reasoning